Reliable estimation of the column density in smoothed particle hydrodynamic simulations - Young, Matthew D.; Bertram, Erik (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. We describe a simple method for estimating the vertical column density in smoothed particle hydrodynamic simulations of discs. As in the method of St
Gesehen am 16.08.2018